Genetically transitional disease: a new concept in genomic medicine. Issue 2 (February 2023) - Yao, Qingping; Gorevic, Peter; Shen, Bo; Gibson, Greg
Highlights: The traditionally dichotomous classification of monogenic or polygenic/genetically complex disease lags far behind the scientific discovery of tens of thousands of gene mutations associated with existing and emergent human genetic diseases. The pervasive influence of genetic background on both penetrance and expressivity of mutations in diseases also calls for revision of the disease nosology. We propose a new terminology, genetically transitional disease (GTD), to denote a disease status between monogenic and polygenic disease where a mutation is necessary, but not sufficient, to cause and define the disease. The new concept and nosology are envisioned with respect to four scenarios that are exemplified by various diseases. These are discussed with regard to therapeutic implications for the implementation of personalized medicine. Abstract: Traditional classification of genetic diseases as monogenic and polygenic has lagged far behind scientific progress. In this opinion article, we propose and define a new terminology, genetically transitional disease (GTD), referring to cases where a large-effect mutation is necessary, but not sufficient, to cause disease. This leads to a working disease nosology based on gradients of four types of genetic architecture: monogenic, polygenic, GTD, and mixed. We present four scenarios under which GTD may occur; namely, subsets of traditionally Mendelian disease, modifiable Tier 1 monogenic conditions, variable penetrance, and situations where a genetic mutational spectrum produces qualitatively divergent pathologies. The implications of the new nosology in precision medicine are discussed, in which therapeutic options may target the molecular cause or the disease phenotype.